Catalytic Asymmetric Synthesis of All Possible Stereoisomers of 2, 3, 4, 6‐Tetradeoxy‐4‐Aminohexopyranosides. Issue 11 (14th April 2018) - Zhu, Zhongpeng; Glazier, Daniel A.; Yang, Daoshan; Tang, Weiping
Abstract: We recently developed a divergent strategy for the synthesis of all eight possible 2, 3, 6‐trideoxyhexopyranosides with three stereogenic centers. However, the diastereoselectivity for one of the three stereogenic centers was low and it was not controlled by catalysts. In this update, we described a systematic method for the first catalytic asymmetric synthesis of all eight possible 2, 3, 6‐trideoxyhexopyranosides and all eight possible 2, 3, 4, 6‐tetradeoxy‐4‐aminohexopyranosides. The products derived from this strategy include the glycone of natural products grecocycline A, spinosyn A, and ossamycin. All three stereogenic centers in each product was controlled by a pair of chiral catalysts. The key to the success is the application of our recently developed dynamic kinetic stereodivergent acylation of Achmatowicz rearrangement products and chiral catalyst‐directed reduction. Simple dimethylation of the 2, 3, 4, 6‐tetradeoxy‐4‐amino sugars afforded derivatives of naturally occurring β‐D‐forosaminide and β‐L‐ossaminide. Abstract :